Activin A promoted the anti‐tumor effect of ActRIIA high CD8+ T cells in mouse hepatoma - Liangchang Hu; Yu Zhao; Xuguang Zhang; Chunhui Ma (Cancer Medicine)
Abstract Background Activin A, a noteworthy member of the TGF‐β superfamily. Activin A can regulate the biological functions of various immune cells, such as macrophages, neutrophils, NK cells, etc. The purpose of this study is to investigate the regulatory effect and related mechanisms of activin A on CD8+ T cells. Methods This study established a mouse subcutaneous transplantation model of hepatoma to explore whether activin A has a regulatory effect of CD8+ T cells. And reveal the biological characteristics of ActRIIA high CD8+ T cells. Results We discovered that CD8+ T cells express ActRIIA, ActRIIB, and Smad2,3,4. Unlike high‐dose activin A, low‐dose activin A increased the content of CD8+ T cells while also suppressing tumor growth. In addition, low‐dose activin A promoted expression of perforin, granzyme B, CD69, CD11c, CD49b, Ki67 and ActRIIA in CD8+ T cells. And the results indicated that high‐dose activin A promotes the expression of PPM1A in T cells, while low‐dose activin A has no effect on these cells. The tumor contained more ActRIIA high CD8+ T cells compared to the peripheral blood and spleen. ActRIIA high CD8+ T cells highly express cytotoxic molecules and cytokines. And ActRIIA high CD8+ T cells not only expressed high levels of activation/co‐stimulatory markers CD69, CD278, and CD28, but also high levels of inhibitory markers CD366 and KLRG1. Different chemokine receptors displayed varying levels of expression in ActRIIA high CD8+ T cells. Additionally, these cells have a high proliferative potential. Finally, overexpression of Mettl3 inhibited the expression of ActRIIA in CD8+ T cells. Conclusions This study demonstrated that low‐dose activin A enhanced the anti‐tumor effect of CD8+ T cells, and ActRIIA high CD8+ T cells actively contribute to tumor immunity.